DIGITAL FINANCIAL LITERACY AND GEN Z FINANCIAL WELL-BEING IN BANYUMAS: THE ROLE OF BEHAVIOR AND SKILLS - Nina Fidiawati; Wida Purwidianti (Finansha: Journal of Sharia Financial Management, 2026)
This study analyzes the influence of digital financial literacy (DFL) on the financial well-being (FWB) of Generation Z e-wallet users in Banyumas Regency, mediated by financial behavior (FB) and financial skill (FS), with gender as a control variable. The research gap stems from the inconsistency of DFL's direct influence on FWB in the previous literature and the limitations of empirical locus, which are mostly centered in metropolitan areas. Its novelty lies in the exploration of non-metropolitan areas where rapid adoption of technology occurs amid limited structural income. Using a cross-sectional quantitative survey design, data from 153 Gen Z respondents aged 18–29 years were collected through purposive sampling and analyzed using PLS-SEM via SmartPLS 3. The results showed that DFL had no direct effect on FWB. Conceptually, this is crucial, confirming that digital knowledge fails to guarantee real well-being in the absence of operational execution capacity. Further, FS acted as a full mediator, while FB failed to mediate. FS emerged as a much stronger FWB predictor than FB. A R^2value of 0.688 indicates that the model is able to explain 68.8% of the FWB variance. Theoretically, this strengthens the Capability Approach and Human Capital Theory, proving that functional technical capacity is much more vital in converting knowledge capital into welfare outputs than just routine behavioral intentions. Practically, the study suggests a shift in regional education and banking policies from cognitive-theoretical literacy towards technical-practical skills training in e-wallet optimization to achieve substantive financial inclusion for regional Gen Z.